Effect of single-patient room design on the incidence of nosocomial infection in the intensive care unit: a systematic review and meta-analysis - Zhang, Zheng; Tan, Xiaojiao; Shi, Haiqing; Zhao, Jia; Zhang, Huan; Li, Jianbo; Liao, Xuelian (Frontiers in Medicine, 2024)
Background Previous studies have yielded varying conclusions regarding the impact of single-patient room design on nosocomial infection in the intensive care unit (ICU). We aimed to examine the impact of ICU single-patient room design on infection control. Methods We conducted a comprehensive search of PubMed, Embase, the Cochrane Library, Web of Science, CNKI, WanFang Data, and CBM databases from inception to October 2023, without language restrictions. We included observational cohort and quasi-experimental studies assessing the effect of single- versus multi-patient rooms on infection control in the ICU. Outcomes measured included the nosocomial infection rate, incidence density of nosocomial infection, nosocomial colonization and infection rate, acquisition rate of multidrug-resistant organisms (MDROs), and nosocomial bacteremia rate. The choice of effect model was determined by heterogeneity. Results Our final analysis incorporated 12 studies involving 12,719 patients. Compared with multi-patient rooms in the ICU, single-patient rooms demonstrated a significant benefit in reducing the nosocomial infection rate (odds ratio [OR]: 0.68; 95% confidence interval [CI]: 0.59, 0.79; p < 0.00001). Analysis based on nosocomial infection incidence density revealed a statistically significant reduction in single-patient rooms (OR: 0.64; 95% CI: 0.44, 0.92; p = 0.02). Single-patient rooms were associated with a marked decrease in nosocomial colonization and infection rate (OR: 0.44; 95% CI: 0.32, 0.62; p < 0.00001). Furthermore, patients in single-patient rooms experienced lower nosocomial bacteremia rate (OR: 0.73; 95% CI: 0.59, 0.89; p = 0.002) and lower acquisition rate of MDROs (OR: 0.41; 95% CI: 0.23, 0.73; p = 0.002) than those in multi-patient rooms. Conclusion Implementation of single-patient rooms represents an effective strategy for reducing nosocomial infections in the ICU. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/).